Distribution, ecology, life history, genetic variation, and risk of extinction of nonhuman primates from Costa Rica - María E Zaldívar (Revista de Biología Tropical, 2004)
We examined the association between geographic distribution, ecological traits, life history, genetic diversity, and risk of extinction in nonhuman primate species from Costa Rica. All of the current nonhuman primate species from Costa Rica are included in the study; spider monkeys (Ateles geoffroyi), howling monkeys (Alouatta palliata), capuchins (Cebus capucinus), and squirrel monkeys (Saimiri oerstedii). Geographic distribution was characterized accessing existing databases. Data on ecology and life history traits were obtained through a literature review. Genetic diversity was characterized using isozyme electrophoresis. Risk of extinction was assessed from the literature. We found that species differed in all these traits. Using these data, we conducted a Pearson correlation between risk of extinction and ecological and life history traits, and genetic variation, for widely distributed species. We found a negative association between risk of extinction and population birth and growth rates; indicating that slower reproducing species had a greater risk of extinction. We found a positive association between genetic variation and risk of extinction; i.e., species showing higher genetic variation had a greater risk of extinction. The relevance of these traits for conservation efforts is discussed. Rev. Biol. Trop. 52(3): 679-693. Epub 2004 Dic 15. Se estudió la asociación entre la distribución geográfica, algunos rasgos ecológicos, las historias de vida, la diversidad genética y el riesgo de extinción, en primates no humanos de Costa Rica. Se incluyen todas las especies de primates no humanos del país: los monos araña (Ateles geoffroyi), congo (Alouatta palliata), cara blanca (Cebus capucinus), y tití (Saimiri oerstedii). La distribución geográfica se caracterizó utilizando principalmente bases de datos existentes. Se obtuvo información acerca de sus características ecológicas y de historias de vida mediante una revisión bibliográfica. Se estudió su diversidad genética utilizando electroforesis de isoenzimas. El riesgo de extinción se evaluó usando información bibliográfica. Se encontró que las cuatro especies presentaban variación en todos estos rasgos. Con estos datos, se realizó una correlación de Pearson entre el riesgo de extinción y las variables indicadoras de la distribución geográfica, los rasgos ecológicos, las historias de vida y la diversidad genética, para aquellas especies con una amplia distribución geográfica. Se encontró una asociación entre el riesgo de extinción y la natalidad y la tasa de crecimiento poblacional; las especies con menor natalidad y menor tasa de crecimiento poblacional tenían mayor riesgo de extinción. Se encontró una asociación positiva entre la diversidad genética y el riesgo de extinción; las especies con mayor diversidad genética tenían mayor riesgo de extinción. Se discute la importancia de estos rasgos para la conservación de estas especies.